A Study on Consumer Buying Behavior towards Wai Wai Noodles in Kathmandu Valley - Shrestha, Mikha (Management Dynamics, 2018)
This research overviews buying behaviours and their relations to the levels of consumer satisfaction. While approaching consuming behaviour, the researcher studies not only the act of purchase, but also the pre-purchase stage and post-purchase one. Only the whole study of buying behaviors gives a possibility to determine the relationship between buying behaviors and consumer satisfaction. This paper is aimed to showing that, while buying behaviors can be pre-determined to some extent, it is hard to manipulate them in order to increase satisfaction. In order to ensure customer satisfaction with products and services it is essential to study customer behaviors in a particular market and adjust the product according to them. The study focuses on the consumer’s buying behavior towards, ‘brand’ Wai Wai instant noodle in Kathmandu Valley and the reason behind its popularity, than other noodle across the consumers. Fast foods are the foods that can be prepared quickly and junk foods are the preprepared or packaged food. These foods do not take much time to cook and are also tasty, so they are quite popular among the people of every age group. The market of the junk foods is growing every year. There are a number of junk food production companies in the market and they are growing in size with the growing popularity of the junk foods. The noodles companies are producing noodles in large variety and taste so that the consumers of the noodles never get bored by the same taste every time. This has led to the increase of the noodles market globally. The market of Nepalese noodles companies have not only been limited within the country’s boundary but also it has been exporting its products to various countries. It still has the potential and scope to expand more.